Physical activity and the Body Mass Index in Physical Education students - Contreras-Canto, Omar H. (2024)
In the present study we delve into the importance of physical activity in the school context since it favors the improvement of health. The objective of this study was to determine the relationship between physical activity and the Body Mass Index in students aged 10 to 13 years of the National College of Application of the National University Hermilio Valdizán. The study was descriptive with a causal correlational design, the sample included 121 students, the data collected was through a questionnaire and BMI form. Finding as a result that the majority of students surveyed show a normal BMI (18.50 to 24.99) according to age, weight and height, where it is stated that there is agreement with the practice of some physical activity, corroborated by the calculated value of the Chi square test. equal to 8.37 which is greater than the critical value of 7.81. Which leads to the conclusion that there is a significant relationship between physical activity and BMI in students from 10 to 13. Likewise, it is evident that physical activity in students is in acceptable terms in terms of type, continuity, duration and intensity, showing that they are aware of performing exercises in Physical Education hours according to the virtual strategy of learning at home, they perform aerobic exercises on their own initiative, showing a period of time to perform them and above all they feel concerned about improving their fitness for health.